The asymmetric synthesis of amino acids via glycine enolates - Im, Myeong-Nyeo, author; Williams, Robert M., advisor (Colorado State University. Libraries, 1991)
The enolates derived from the optically active D-e rythro-4- (tertbutyloxycarbonyl)-5,6-di phenyl-2,3,5,6-tetrahydro-4H-1,4-oxazin-2-one (166a) and D- and L-erythro-4-(benzyloxycarbonyl)-5,6-diphenyl-2,3,5,6- tetrahydro-4H-1,4-oxazin-2-ones (167a/b) efficiently couple with alkyl halides to afford the corresponding anti-α-monosubstituted oxazinones. The enolate alkylation of the a-monosubstituted oxazinones provides the corresponding α-disubstituted oxazinones. Dissolving-metal reduction of the homologated oxazinones allows the direct preparation of t-BOC protected α-amino acids. In the case of dissolving metal-reducible functionality, hydrogenation over a Pd° catalyst furnishes the zwitterionic amino acids. By employing this protocol the syntheses of complex amino acids such as 2-(tert-butyloxycarbonyl)amino-6-(p-methoxybenzyI)thionohexanoic acid and 2,6-diamino-6-hydroxymethylpimelic acid are discussed.
Keywords: Amino acids -- Synthesis; Glycine; Organic compounds -- Synthesis